Musical memories of Nigeria - Kingslake, Brian (International Library of African Music, 1957)
Most of the instruments I heard were percussive. There were the ordinary tomtom and drum, and some extraordinary drums carved for juju ceremonial. There were logs of wood hollowed out through a slot, with one “cheek” thinner than the other and thus giving a higher note when struck. Then there was the Ilu or dundun drum. The wooden part is shaped like an hour glass; there is a skin head at each end, the skins being joined together all round by thonging. You hold it under your left arm and strike the upper head with a drumstick curved like a crane’s bill; by squeezing and relaxing the arm pressure on the thongs, you can raise or lower the pitch of the note. The result is an intriguing “pop pop pop” running with great mobility up and down over a range of a full fifth. This instrument is used also as a “talking drum” for conveying messages. Rattles? All sorts. One like a pepper pot containing seeds. One a gourd or calabash covered with a bead net which rattles beautifully when shaken. Or a species of nut shells strung together, which make an almost deafening row. Then there are gongs: round, square or flat, of iron or brass. Every senior Chief has his private band, which plays perpetually; also a bard to sing his praises. There are traditional songs for every occasion: birth, initiation, marriage, death, the propitiation of ancestors, and so on. Cult groups have their own songs; and different kinds of song are sung with a different quality of voice.
Keywords: Talking drum; African Music; Nigeria; Musical Memory